ABILITY TO KNOW LETTERS THROUGH LETTER CARD GAME IN GROUP A IN PAUD DARUSALAM AR-RIZKI GEDONGTATAAN - Sari, Nur Indah Kurnia Alfazri (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2020)
Playing activities are a very effective way to develop the potential that exists in children. This is in accordance with the principles of learning in kindergarten education, where early childhood education is playing while learning, learning while playing. However, in reality, the teacher has not been able to develop ideas that can develop aspects of child development in learning activities, especially in recognizing letters so that the child's ability to recognize letters is still low and the way of pronouncing it is also unclear. This study aims to improve the ability to recognize letters (mentioning letters, show letters, and connect letters) by using letter cards in early childhood group A in PAUD Darusalam Ar-Rizki.This type of research is classroom action research conducted collaboratively between researchers and class teachers. This Classroom Action Research consists of four important stages, namely: planning, implementing, observing, and reflecting and using 2 cycles. For the research object were students and female students of group A as many as 18 children. Data collection techniques in this study through observation, interviews and documentation. The results of this study indicate that the ability to recognize letters of group A children in PAUD Darusalam Ar-Rizki can be improved using letter card media. In the learning process of guessing letters on letter cards, each child carries or holds the letter card directly and plays it according to the teacher's instructions, namely mentioning letters, showing letters, and connecting letters. The results of this study indicate that there is an increase in the ability to recognize letters, namely in the pre-cycle by 22.6%, increasing in Cycle I to 54.8%, and in Cycle II an increase of 98.2%. From this explanation, it can be understood that the increase in pre cycle to cycle I was 41.2%, and from cycle I to cycle II increased by 53.7%. So it can be concluded that the ability to recognize letters in group A children in PAUD Darusalam Ar-Rizki can be improved through letter card game media.